Moderation Role of Teacher-Student Relationships on Correlation between L2 Motivation and L2WTC - Nugroho, Dhimas Cahyo; Fahri, Fahri; Zuhri, Fauris; Sumarniningsih, Sumarniningsih (Journal of Languages and Language Teaching, 2024)
Large body of researches has been consistently linked L2 motivation to L2WTC, indicating a significant positive correlation between the two. Yet, the influence of teacher-student relationships on this correlation remains understudied. This research investigates how teacher-student relationships influences the correlation between L2 motivation and L2WTC, as well as to investigate the variations in this influence across varying qualities of teacher-student relationships. Utilizing established scales, questionnaires were distributed to the entire population of SMP Negeri 51 Surabaya, resulting in 222 responses for analysis. Moderation analysis via regression analysis was employed to analyse the data. The findings showed that teacher-student relationships do not significantly moderate the correlation between students' L2 motivation and their L2WTC, nor do they significantly differ in influence across varying qualities. Although statistical significance was not achieved at the conventional threshold, the study hints the potential significance of teacher-student relationships in sustaining L2WTC, particularly in contexts where L2 motivation may be lacking. Thus, while not meeting statistical significance at conventional thresholds, the results underscore the importance of fostering positive teacher-student relationships in language learning contexts.